Comparing Factors Influencing Heavy Episodic Drinking of Young Adults in the United Kingdom and The Netherlands. Issue 6 (28th August 2020) - Liebrand, Sil; Eberhardt, Judith; van Schaik, Paul; Pieterse, Marcel; van Wersch, Anna; ten Klooster, Peter; Boer, Henk
Abstract: The United Kingdom and the Netherlands exhibit similar levels of heavy episodic drinking but different drinking patterns among youths. This study aimed to assess the impact of country of residence on heavy episodic drinking among 293 British and Dutch youths, accounting for other behavioral determinants. Participants completed online questionnaires measuring impulsivity, sensation-seeking, alcohol consumption, and constructs from the Theory of Planned Behavior [TPB]. Mediation analysis established that British youths engaged in more frequent heavy drinking episodes than Dutch youths, as they had weaker intentions to refrain from heavy drinking, and lower perceived behavioral control. Country of residence also was a direct predictor of frequency of heavy drinking episodes, not mediated by personality traits. Thus, country of residence seems an important factor in heavy episodic drinking, partly mediated through TPB constructs. Interventions may benefit from targeting country-specific drinking behavior and related socio-psychological mechanisms.